2004
DOI: 10.1111/j.1525-1497.2004.30613.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in san francisco’s HIV-infected urban poor

Abstract: While HCV infection is common, HCV treatment is rare in the HIV-HCV coinfected urban poor. Urban poor, nonwhite individuals are less likely to receive HCV testing and subspecialty referral than their white counterparts. Antibody-negative infection may complicate screening and diagnosis in HIV-infected persons. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 85 publications
8
80
1
1
Order By: Relevance
“…Hall et al [4] found that only 68% of the coinfected patients in the REACH cohort were aware of the possibility of treatment for HCV, and only 3.8% had previously been treated. Nonwhites were found to be less likely to be tested for HCV and to receive subspecialty referral upon testing HCV positive.…”
Section: Physician and Patient Barriers To Treatment Of Hcv In Coinfementioning
confidence: 99%
See 1 more Smart Citation
“…Hall et al [4] found that only 68% of the coinfected patients in the REACH cohort were aware of the possibility of treatment for HCV, and only 3.8% had previously been treated. Nonwhites were found to be less likely to be tested for HCV and to receive subspecialty referral upon testing HCV positive.…”
Section: Physician and Patient Barriers To Treatment Of Hcv In Coinfementioning
confidence: 99%
“…Hall et al [4] report a baseline prevalence rate of 69% coinfection with HCV in a sample of 249 persons enrolled in the Research and Access to Care for the Homeless (REACH) cohort of HIV-infected marginally housed individuals in San Francisco. Of those with an IDU history the coinfection rate was 79%, whereas it was 21% among those without IDU history.…”
Section: Prevalence and Incidence Of Coinfectionmentioning
confidence: 99%
“…2 This number may be even higher when homeless and incarcerated persons are taken into account, as infection rates in these populations may exceed 40% [3][4][5][6] and even 70% among human immunodeficiency virus-positive (HIV ϩ ) urban poor. 7 Overall, approximately 85% of those with an acute infection will develop chronic disease, 8 persistent viremia occurring at least 6 months after initial exposure, with estimates ranging from 55% in the Irish anti-D immune globulin cohort 9 and 60% in a study of community-acquired HCV in the United States 10 to 90% in a single-source outbreak from contaminated clotting factors in Austria. 11 Fortunately, HCV incidence has dropped nearly 10-fold in the United States since the 1980s, 12 largely because of improved screening of blood products, decreased injection drug use (IDU), and safer sexual practices.…”
Section: Epidemiology and Natural History Of Hcv Infectionmentioning
confidence: 99%
“…In addition, in co-infected patients, HCV can increase morbidity and mortality related to HIV (12) . The efficacy of the treatment for hepatitis C can vary among patients, and genetic characteristics play an important role in the response to the drugs used.…”
Section: Frequency Of the Mdr1 Gene Polymorphism Rs1045642 (C3435t) Imentioning
confidence: 99%